2019
DOI: 10.5530/pj.2019.11.103
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Survey of the Medicinal Plants used in the Southern Mediterranean. Case Study: The Region of Bissa (Northeastern Dahra Mountains, Algeria)

Abstract: Introduction: The present study falls within the framework of valorization of medical plants and traditional knowledge's in the Northeastern part of Dahra Mountain, Algeria. Methods: An ethnobotanical survey was conducted between 2016 and 2018 in order to study the traditional and therapeutic use of medical plants amongst the local population. Data collected was analyzed using quantitative indices such as the fidelity level (FL) and Informant Consensus Factor (FIC). Results:The results revealed 70 medicinal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(41 citation statements)
references
References 47 publications
(97 reference statements)
4
36
0
1
Order By: Relevance
“…Several cited chemical compositions of P. halepensis have been published regarding terpenes, fatty acids, aldehydes, and cyclic phenolic compounds [59][60][61]. The lipophilic extractives (resin acids, terpenes, fatty acids, glycerides, steryl esters, sterols) were extracted using n-hexane then the hydrophilic ones (stilbenes, flavanols, monosaccharides, sugar alcohols) with acetone/water from sapwood and heartwood of P. halepensis stem [62].…”
Section: Discussionmentioning
confidence: 99%
“…Several cited chemical compositions of P. halepensis have been published regarding terpenes, fatty acids, aldehydes, and cyclic phenolic compounds [59][60][61]. The lipophilic extractives (resin acids, terpenes, fatty acids, glycerides, steryl esters, sterols) were extracted using n-hexane then the hydrophilic ones (stilbenes, flavanols, monosaccharides, sugar alcohols) with acetone/water from sapwood and heartwood of P. halepensis stem [62].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been carried out on the physicochemical quality and the antibacterial and antifungal power of medicinal plants oils. Most of researches conducted were devoted to ethnobotanical studies which have become increasingly important in recent decades, particularly in North Africa and Algeria (Fakchich and Elachouri, 2014;Boughrara and Legseir, 2016;Rhattas et al, 2016;Bouasla and Bouasla, 2017;Katiri et al, 2017;Miara et al, 2018;Lazli et al, 2019;Senouci et al, 2019;Zahir et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the high antioxidant capacity of the plant species (Longo et al, 2007;Arab et al, 2014;Dahmoune et al, 2014;Djedaia 2017). Senouci et al, (2019) reported that aerial parts contain terpineol, which is known to be effective against microbial activity. From the literature reviewed, it appears that Pistacia lentiscus leaves have a higher yield of phenolic compounds than fruits or essential oils (Arab et al, 2014;Bampouli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations